Compact and Resource Efficient Cities? Synergies and Trade-offs in European Cities - Fertner, Christian; Große, Juliane (European Spatial Research and Policy, 2016)
Cities are the main consumers of energy and resources but at the same time are considered as centres for innovation which can provide solutions to unsustainable development. An important concept regarding energy and resource efficiency on the scale of the city and city-region is the compact city. Compact cities and compact urban development are thought to decrease energy and resource demand per capita and increase efficiency. At the same time trade-offs and potential rebound effects of increased resource efficiency question certain achievements of a compact urban structure. This paper reviews aspects of resource and energy efficiency in compact city development in a European context. We conclude that, if the idea of the compact city should have any effect on resource and energy efficiency, accompanying measures have to be implemented, such as e.g. efficient public transport systems to offer alternative travel modes. Also the allocation of efficiency gains due to compact urban development has to be taken into account in order to avoid direct and indirect rebound effects.